2013
DOI: 10.1080/17470218.2013.780085
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic and Phonological Preview Benefits: Parafoveal Processing in Skilled and Less-Skilled Deaf Readers

Abstract: Many deaf individuals do not develop the high-level reading skills that will allow them to fully take part into society. To attempt to explain this widespread difficulty in the deaf population, much research has honed in on the use of phonological codes during reading. The hypothesis that the use of phonological codes is associated with good reading skills in deaf readers, though not well supported, still lingers in the literature. We investigated skilled and less-skilled adult deaf readers’ processing of orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 36 publications
10
72
2
Order By: Relevance
“…Together with previous findings (Bélanger, Mayberry, & Rayner, 2013a;Morford et al, 2011;Yan et al, 2015), our results suggest that deaf readers are flexible in the ways that they choose to code words. …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Together with previous findings (Bélanger, Mayberry, & Rayner, 2013a;Morford et al, 2011;Yan et al, 2015), our results suggest that deaf readers are flexible in the ways that they choose to code words. …”
Section: Discussionsupporting
confidence: 89%
“…Recent experiments have further tested the types of information that can be parafoveally obtained by deaf readers: Bélanger, Mayberry, and Rayner (2013a) provided no evidence for parafoveal phonological processing among deaf readers. It is possible that given the lack of auditory input, deaf readers may develop a different coding strategy and/or more direct access to semantics.…”
Section: Parafoveal Processing Of Deaf Readersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bélanger, Baum and Mayberry (2012) concluded that skilled deaf readers might activate visual, orthographic and semantic codes during reading, but not phonological codes in French. Furthermore, Bélanger, Mayberry and Rayner (2013) investigated the phonological and orthographic preview benefit in parafovea in English readers.…”
Section: Introductionmentioning
confidence: 99%
“…Instead they observed a reliance on orthographic codes for word recognition (faster lexical decision latencies following O+P+ than O−P+ primes) and short-term memory maintenance (better recall of words from O+P+ lists than O−P+ lists). Relatedly, both skilled and less skilled deaf readers show orthographic preview benefit but not phonological preview benefit during English sentence reading (Bélanger, Mayberry, & Rayner, 2013). …”
Section: Introductionmentioning
confidence: 99%